1991
DOI: 10.3109/02713689109007608
|View full text |Cite
|
Sign up to set email alerts
|

Cystatins in human tear fluid

Abstract: The activities of cysteine proteinases which include several lysosomal cathepsins are controlled by naturally occurring inhibitory proteins termed cystatins. Cystatins occur both intracellularly and extracellularly in various tissue fluids including tears. Tears were collected by the Schirmer paper strip method from healthy volunteers who had no history or signs of external ocular disease. The tear components were extracted from the filter papers, and used to determine the apparent free cystatin activity and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 12 publications
4
25
0
Order By: Relevance
“…Complex formation of cystatins in tears with increased amounts of cystine proteinases would protect the eye; however, the demonstration of cystatins in the papain assay would be complicated by the masking of the free cystatins. It has been demonstrated that cystatin levels measured by enzyme immunoassay in tears were much higher than that calculated from papain inhibitory assays [8]. This suggests that tears contain immunologically reactive bound cystatins in addition to free cystatins.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Complex formation of cystatins in tears with increased amounts of cystine proteinases would protect the eye; however, the demonstration of cystatins in the papain assay would be complicated by the masking of the free cystatins. It has been demonstrated that cystatin levels measured by enzyme immunoassay in tears were much higher than that calculated from papain inhibitory assays [8]. This suggests that tears contain immunologically reactive bound cystatins in addition to free cystatins.…”
Section: Discussionmentioning
confidence: 93%
“…Cystatins firstly were discovered in chicken egg white, but are also widely distributed in mammalian tissue and can be found in body fluids including the tears [7]. Human tears contain a mixture of cystatin S, cystatin SN, and cystatin C, secreted by the lacrimal gland and not derived from corneal or conjunctival epithelial cells [8]. Cystatins in tears most likely have a protective role against the harmful effects of cysteine proteinases.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of cysteine proteinases is controlled by their physiological inhibitors, the cystatins, which are known to be generally present in tears. 22 Extracellular cystatins have a protective role against the damaging effects of lysosomal proteinases, which can be secreted under physiological conditions for the degradation and regeneration of tissues, as well as under pathological conditions associated with infection by bacteria or viruses, or with the corneal and conjunctival epithelium. 23 The decreased levels of cystatins that we found in KC tears is indicative of an increase in the degradation of tear proteins, which would explain the decrease that we found in the concentration of total protein in KC tears.…”
Section: Discussionmentioning
confidence: 99%
“…This function contributes to prevention of uncontrolled proteolysis and tissue damage [29][30][31]. The expression of these proteins in tears is also known to be reduced in several pathological conditions [32][33][34][35].…”
Section: Cystatin S and Lactoferrinmentioning
confidence: 99%